Automating and estimating glomerular filtration rate for dosing medications and staging chronic kidney disease - Trinkley, Katy E (Dove Medical Press, 2014)
OBJECTIVE: The purpose of this paper is to serve as a review for primary care providers on the bedside methods for estimating glomerular filtration rate (GFR) for dosing and chronic kidney disease (CKD) staging and to discuss how automated health information technologies (HIT) can enhance clinical documentation of staging and reduce medication errors in patients with CKD. METHODS: A nonsystematic search of PubMed (through March 2013) was conducted to determine the optimal approach to estimate GFR for dosing and CKD staging and to identify examples of how automated HITs can improve health outcomes in patients with CKD. Papers known to the authors were included, as were scientific statements. Articles were chosen based on the judgment of the authors. RESULTS: Drug-dosing decisions should be based on the method used in the published studies and package labeling that have been determined to be safe, which is most often the Cockcroft–Gault formula unadjusted for body weight. Although Modification of Diet in Renal Disease is more commonly used in practice for staging, the CKD–Epidemiology Collaboration (CKD–EPI) equation is the most accurate formula for estimating the CKD staging, especially at higher GFR values. Automated HITs offer a solution to the complexity of determining which equation to use for a given clinical scenario. HITs can educate providers on which formula to use and how to apply the formula in a given clinical situation, ultimately improving appropriate medication and medical management in CKD patients. CONCLUSION: Appropriate estimation of GFR is key to optimal health outcomes. HITs assist clinicians in both choosing the most appropriate GFR estimation formula and in applying the results of the GFR estimation in practice. Key limitations of the recommendations in this paper are the available evidence. Further studies are needed to better understand the best method for estimating GFR.